Catheter Ablation of Atrial Fibrillation with Short Duration Radiofrequency Current using Non-Irrigated Catheters - Maryna S. Meshkova; Oleksandr V. Doronin (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. The use of high-power radiofrequency current is considered to be a promising alternative to the currently used technique of catheter ablation of atrial fibrillation (AF) with radiofrequency current of normal power. To date, there are no studies on the application of this technique using catheters without external irrigation.The aim. To study direct results of application of high-power radiofrequency current in AF catheter ablation using non-irrigated catheters.Materials and methods. We analyzed 30 consecutive patients who underwent primary catheter ablation (12 women and 18 men, mean age of the patients was 57.6 ± 11.7 years). Concomitant pathology (coronary heart disease, hypertension, diabetes mellitus) was observed in 19 (63.3%) patients.Wide isolation of pulmonary veins was performed, and in nonparoxysmal forms, applications were added in the places where fragmented activity was registered or in the line of applications between ipsilateral pulmonary veins and inferior left pulmonary vein and mitral valve annulus. The applications were made with a 4 mm electrode without irrigation function with wiping it after every 30 applications. Application parameters were 40-45 Watt power, application time 10 seconds, target temperature 55°C.Results. The mean left atrial catheter dwelling time was 1.6 ± 0.3 hours. The mean time of X-ray exposure was 8.2 ± 2.3 minutes. The average number of applications was 127.8 ± 23.6. It was not possible to isolate 3 pulmonary veins in three patients: one superior left pulmonary vein and two inferior right pulmonary veins (2.5% of all pulmonary veins).No complications related to the procedure were observed. The occurrence of AF in the early postoperative period was observed in 4 (13.3%) patients.Conclusions. The immediate results of applying the radiofrequency current of 40-45 W with the application duration of 10 seconds and the target temperature of 55°C during AF catheter ablation using non-irrigated catheters indicate the safety of this technique. It is necessary to study a larger contingent of patients and long-term results.